Generation of Digital Pulse Width Modulation (DPWM) with TMS320F2812 Digital Signal Processor - Mohd Faridun Naim, Tajuddin; M. S., Azizan; Mohd Fayzul, Mohammed; Baharuddin, Ismail; Siti Rafidah, Abdul Rahim; Mohd Rafi, Adzman; Zainuddin, Mat Isa; Syahrul Ashikin, Azmi; Ismail, Daut (Universiti Malaysia Pahang (UMP), 2010)
MUCEET 2009 is organized by Malaysian Technical Universities Network (MTUN) comprising of Universiti Malaysia Perlis (UniMAP), Universiti Tun Hussein Onn (UTHM), Universiti Teknikal Melaka (UTeM) and Universiti Malaysia Pahang (UMP), 20th - 22nd June 2009 at M. S. Garden Hotel, Kuantan, Pahang.